1993
DOI: 10.1021/tx00032a014
|View full text |Cite
|
Sign up to set email alerts
|

Application of Raney nickel to measure adducts of styrene oxide with hemoglobin and albumin

Abstract: Adducts of styrene 7,8-oxide (SO) with the blood proteins, Hb and albumin (Alb), were measured following treatment of the proteins with Raney nickel (Ra-Ni) to cleave 2-phenylethanol, which was subsequently assayed. Internal standards were prepared by modifying Hb and Alb with 4-methyl-SO to produce similar adducts. In a preliminary experiment with human blood, which had been modified with [14C]SO in vitro, it was determined that Ra-Ni released 6% of the total binding to globin and 76% of the total binding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 21 publications
4
37
0
Order By: Relevance
“…The reagents used for the protein-adduct analyses were the same as those reported by Rappaport et al [17]. The protein-bound internal standards, 4-methyl-SO-Alb and 4-methyl-SO-Hb, were formed by reaction of an aqueous solution of either Alb or globin with 4-methyl-SO.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reagents used for the protein-adduct analyses were the same as those reported by Rappaport et al [17]. The protein-bound internal standards, 4-methyl-SO-Alb and 4-methyl-SO-Hb, were formed by reaction of an aqueous solution of either Alb or globin with 4-methyl-SO.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…In animal experiments it has been demonstrated that both styrene and SO produce cysteine adducts in albumin (Alb) and hemoglobin (Hb) [17,22], N-terminal valine adducts in Hb [11], and carboxylic acid adducts in Hb [19]. However, applications of these assays to styrene-exposed workers in the reinforced-plastics industry have produced inconsistent results [2,3,19,20,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, modified Edman degradation and Raney Nickel procedures have been widely used for the biological monitoring of exposed workers (27,(51)(52)(53)(54)(55). Methods based on modified Edman degradation allow for the determination of adducts on the N-terminal Valine of the globin chains.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have successfully applied Raney Ni to cleave cysteinyl adducts in various tissues, i.e., those of styrene 7,8-oxide styrene in blood proteins (Ting et al 1990;Rappaport et al 1993;Yeowell-O'Connell et al 1996), of benzoquinone in blood and bone-marrow proteins Rappaport et al 1996), of chlorinated quinones from PCP in blood and liver proteins (Lin et al 1999;Tsai et al 2001;Waidyanatha et al 1996), and of polychlorinated biphenyl quinones in liver and brain proteins (Lin et al 2000). By administering [ 14 C/ 12 C 6 ]PCP to animals along with the sequential counting scheme shown in Fig.…”
Section: Discussionmentioning
confidence: 99%